Dynamic changes in the chemical composition and metabolite profiles of drumstick (Moringa oleifera Lam.) leaf flour during fermentation. (1st February 2022) - Shi, Honghui; Yang, Endian; Yang, Heyue; Huang, Xiaoling; Zheng, Mengxia; Chen, Xiaoyang; Zhang, Junjie
Abstract: Solid-state fermentation (SSF) using mixed strains can increase the nutritional value and antioxidant content of Moringa oliefera Lam. leaf flour (MLF). However, little is known about the chemical composition and metabolite profiles of MLF during the fermentation process. In this work, mixed strains of Aspergillus Niger, Candida utilis and Bacillus subtilis were inoculated into MLF for SSF. The MLF's contents of crude protein (CP), crude fiber (CF), water soluble carbohydrate (WSC), reducing sugar, tannin and phytic acid all changed significantly as fermentation proceeded. A metabolomic analysis was performed using GC-TOF-MS, resulting in the identification of 347 metabolites. Fermentation with mixed strains significantly affected levels of amino acids, sugars, and organic acids; concentrations of most amino acids, oligosaccharides, organic acids, nucleosides, γ-aminobutyric acid (GABA), and myo-inositol were higher after 3 d of SSF than at the start. Additionally, several intermediate metabolites were detected in 3 d fermented MLF. The mixed microorganisms' metabolic activity thus seems to peak after 3 d of fermentation under the tested conditions. These results provide new insights into the changes in the chemical composition and metabolite content of MLF during SSF and reveal possibilities for producing valuable compounds via this process. Highlights: Solid-state fermentation was conductive to improving drumstick leaf nutritional value. Protein content was increased. Anti-nutritional factors tannins, phytic acid were decreased. Some beneficial metabolites were released during fermentation.